THE NEED TO FORM THE STATE INVESTMENT STRATEGY - Oltaev, Shavkat (Innovative Development in Educational Activities, 2024)
At the current stage, the main global problem of the world economy is to get out of the influence of the corona virus pandemic as soon as possible and further develop the national economy. The estimated pace of recovery is insufficient for global production to return to the 2022 levels predicted before the pandemic began. In addition, the recovery process is still going on in different ways in the countries of the world.